Laparoscopic Valve-Preserving Cecectomy for Fibrous Obliteration of the Appendix Mimicking an Appendiceal Mucocele: A Case Report - Rizky Ratria Kusumawardhani; Anung Noto Nugroho (Open Access Indonesian Journal of Medical Reviews, 2026)
Fibrous obliteration of the appendix is an under-recognized, benign process in which the normal appendiceal mucosa, lymphoid follicles, and submucosa are progressively replaced by fibroblastic and neurogenic tissue. When the obliterated lumen dilates and accumulates low-attenuation material, it can closely imitate an appendiceal mucocele or a low-grade appendiceal mucinous neoplasm on computed tomography (CT), creating a therapeutic dilemma: the surgeon must avoid both under-treatment, which risks a neoplastic margin or pseudomyxoma peritonei, and over-treatment with an unnecessary colectomy. We report a 59-year-old woman with six months of recurrent epigastric and right-lower-quadrant pain and a soft, non-peritonitic abdomen, in whom contrast-enhanced CT showed a well-defined, tubular, fluid-density appendiceal lesion measuring 4.5 × 2.4 × 6 cm extending toward the cecum, with a basal calcific focus and no post-contrast enhancement, interpreted as a probable mucocele. Given its size, basal location, and indeterminate nature, a laparoscopic cecectomy was performed: the mesoappendix and ligament of Treves were sealed and divided, the right colon was mobilized, and the cecum was transected with a linear stapler oriented to preserve the ileocecal valve, with intact en-bloc retrieval in an endobag. Histopathology revealed fibrous obliteration—luminal replacement by spindle cells in a loose fibromyxoid stroma with chronic inflammation and absent normal mucosa—rather than a mucinous neoplasm. Recovery was uneventful, with a one-day stay and resolution of the right-sided pain. Valve-preserving laparoscopic cecectomy is a safe, function-sparing alternative to segmental colectomy for selected benign appendiceal and cecal disease when the base is involved or the diagnosis is indeterminate.